2019
DOI: 10.1002/ppsc.201800420
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Assembled Fluorescent and Antibacterial GHK‐Cu Nanoparticles for Wound Healing Applications

Abstract: GHK‐Cu is demonstrated with the abilities to improve wound healing, accelerate anti‐inflammatory activity, and repair DNA damage. However, the instability of the GHK‐Cu in biological fluids is always a big challenge for its long‐term and efficient function at the target site. Therefore, the self‐assembled GHK‐Cu nanoparticles (GHK‐Cu NPs) are investigated in this work to solve the instability issue. The crystalline nanostructure within the GHK‐Cu nanoparticles offers them visible and near‐infrared fluorescent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 52 publications
0
19
0
Order By: Relevance
“…The formation of the ternary complex may also be of relevance to recent usage of UCA or Cu/GHK in cosmetics, anti-allergic or wound-healing-promoting materials, involving GHK immobilized on polymers or nanoparticles, or within liposomes [ 2 , 6 , 42 , 43 , 44 , 45 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…The formation of the ternary complex may also be of relevance to recent usage of UCA or Cu/GHK in cosmetics, anti-allergic or wound-healing-promoting materials, involving GHK immobilized on polymers or nanoparticles, or within liposomes [ 2 , 6 , 42 , 43 , 44 , 45 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…Subsequent studies found that GHK‐Cu complex can promote wound healing. [ 18–20 ] Sun et al [ 21 ] reported that GHK‐Cu can form blue fluorescent nanoparticles, suggesting that short peptides composed of non‐aromatic amino acids can also form fluorescent nanomaterials through self‐assembly, which overturns the traditional idea that only peptides containing aromatic amino acids can construct fluorescent nanostructure chromophores.…”
Section: Introductionmentioning
confidence: 99%
“…Wound healing includes homeostasis stage (clotting and immune activation), inflammation (recruitment of neutrophilis and macrophages, production of cytokine and growth factor), proliferation phase, tissue neoformation (reepithelialization, angiogenensis and granulation) and subsequent remodeling of neoformed-tissue 1. Considering the crucial barrier role of the skin, nonhealing wounds (such as venous leg ulcers, diabetic foot ulcers, arterial insufficiency and pressure ulcers) and burns impose substantial morbidity and mortality, deeply affecting the quality of life with high economic burden2…”
Section: Introductionmentioning
confidence: 99%